PENGARUH KETERLIBATAN AYAH DALAM PENGASUHAN TERHADAP KONFORMITAS TEMAN SEBAYA - Aries Diyanti, Rizmaya Dewi; Handayani, Arri; Yulianti, Padmi Dhyah (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2026)
This study aims to determine the effect of father involvement on peer conformity in high school students. The research approach is quantitative with a survey method. The research instrument is a scale of father involvement with a reliability of 0.757 and peer conformity with a reliability of 0.698. The sampling technique used purposive sampling with respondents of 211 high school students who live with their fathers and receive direct father care roles. Data analysis used simple linear regression analysis. The results of the study show that father involvement in parenting has a positive effect on student conformity. (R Square = 0.412). Father involvement is not only complementary, but also has a real role in shaping the social behavior of adolescents in the community environment.